Functional analysis of lipid metabolism genes in wine yeasts during alcoholic fermentation at low temperature - María López-Malo; Estéfani García-Ríos; Rosana Chiva; José Manuel Guillamon (Microbial Cell)
Wine produced by low-temperature fermentation is mostly considered to have improved sensory qualities. However few commercial wine strains available on the market are well-adapted to ferment at low temperature (10 – 15°C). The lipid metabolism of Saccharomyces cerevisiae plays a central role in low temperature adaptation. One strategy to modify lipid composition is to alter transcriptional activity by deleting or overexpressing the key genes of lipid metabolism. In a previous study, we identified the genes of the phospholipid, sterol and sphingolipid pathways, which impacted on growth capacity at low temperature. In the present study, we aimed to determine the influence of these genes on fermentation performance and growth during low-temperature wine fermentations. We analyzed the phenotype during fermentation at the low and optimal temperature of the lipid mutant and overexpressing strains in the background of a derivative commercial wine strain. The increase in the gene dosage of some of these lipid genes, e.g., PSD1, LCB3, DPL1 and OLE1, improved fermentation activity during low-temperature fermentations, thus confirming their positive role during wine yeast adaptation to cold. Genes whose overexpression improved fermentation activity at 12°C were overexpressed by chromosomal integration into commercial wine yeast QA23. Fermentations in synthetic and natural grape must were carried out by this new set of overexpressing strains. The strains overexpressing OLE1 and DPL1 were able to finish fermentation before commercial wine yeast QA23. Only the OLE1 gene overexpression produced a specific aroma profile in the wines produced with natural grape must.